(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
It’s known that value and norms in organizations are unwritten rules within the company, to regularize and control employees and their behavior. The objective of this study is learning about how the covid-19’s has impacted on the organization’s social, appearance, work and resource norms within the company. While writing this report, what are the organizational behavior and what might be the example of norms of any company, and how they affect you individual’s life and they are behavior have been learnt. And how pandemic has influenced these factors. It can be seen, learning the impact of covid-19 to the daily life as well as the impact to norms of organization will be helpful to analyze advantages and the disadvantages of coronavirus outbreak in the future. In this focuses on the changes which are happening in social norms regarding to keeping social distance or greetings, changing clothing style and the impact of covid-19 to work norms and unemployment